2003
DOI: 10.1038/sj.npp.1300230
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mood and Cognitive Performance Following Acute Administration of Single Doses of Melissa Officinalis (Lemon Balm) with Human CNS Nicotinic and Muscarinic Receptor-Binding Properties

Abstract: Melissa officinalis (Lemon balm) is a herbal medicine that has traditionally been attributed with memory-enhancing properties, but which is currently more widely used as a mild sedative and sleep aid. In a previous study it was demonstrated that a commercial Melissa extract led to dose-specific increases in calmness, and dose-dependent decrements in timed memory task performance. However, the extract utilized in that study did not exhibit in vitro cholinergic receptor-binding properties. The current study invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
114
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 31 publications
7
114
1
3
Order By: Relevance
“…As an example, while extracts of M. officinalis (also a member of the Labiatae family) have been shown to bind directly to both muscarinic and nicotinic receptors in human brain tissue (eg Kennedy et al, 2003), potential receptor-binding properties (in any neurotransmitter system) have not, as yet, been investigated in extracts of S. officinalis. It therefore seems premature to attribute any effects to a specific mechanism simply on the basis that it has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, while extracts of M. officinalis (also a member of the Labiatae family) have been shown to bind directly to both muscarinic and nicotinic receptors in human brain tissue (eg Kennedy et al, 2003), potential receptor-binding properties (in any neurotransmitter system) have not, as yet, been investigated in extracts of S. officinalis. It therefore seems premature to attribute any effects to a specific mechanism simply on the basis that it has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Since these drugs are associated with serious adverse effects, for example, rebound and hang-over effects, reduced alertness and efficiency during the day as well as physical and psychic addiction, chronic intake of these substances is somewhat problematic. Recent studies demonstrated that herbal preparations containing lemon balm (Melissa officinalis, L.) (Ballard et al, 2002;Kennedy et al, 2003), valerian (Valeriana officinalis, L.) (Cerny and Schmid, 1999) or St John's wort (Kommission E Monograph, 1989) proved as alternatives with satisfying efficacy and tolerability. Also lavender (Lavandula angustifolia, Mill.)…”
Section: Introductionmentioning
confidence: 99%
“…Studies on AChE inhibitor application in healthy participants showed a cognitive impairment rather than an enhancement and a bell‐shaped dose‐response curve has been proposed for the effects of several cholinergic receptor agonists on cognition (Kennedy et al. 2003; Kitagawa et al. 2003; Beglinger et al.…”
Section: Discussionmentioning
confidence: 99%